Assessing the Effect of Green Supply Chain Practices on Corporate Performance in Philippines - Anne , Jasmine (International Journal of Supply Chain and Logistics, 2024)
Purpose: This article evaluated how environmentally sustainable practices impact corporate outcomes. It explores green supply chain strategies like eco-friendly sourcing and waste reduction, examining their effects on financial performance and brand reputation. The study aims to help businesses understand the benefits and challenges of integrating sustainability into their supply chains. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Green supply chain practices positively impact corporate performance by enhancing efficiency, reducing costs, and improving brand reputation. Companies adopting practices like sustainable sourcing and waste reduction report better operational outcomes and increased customer loyalty. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV), stakeholder theory, institutional theory may be used to anchor future studies on the assessing the effect of green supply chain practices on corporate performance. For practitioners, the findings underscore the importance of implementing GSCM practices as part of a long-term strategic framework. At the policy level, governments should provide incentives and subsidies for companies that adopt GSCM practices, particularly in high-impact sectors like manufacturing and textiles.